Peran Perusahaan BUMN dalam Mengakomodasi Kebutuhan Masyarakat Melalui Kegiatan CSR - Raditia Yudistira Sujanto (CHANNEL: Jurnal Komunikasi, 2019)
PT TWC carries out corporate social responsibility activities through a special division namely PKBL. Social programs implemented are mainly of philanthropic activities such as providing assi ance such as educational funding for high-achieving udents, house renovation for members of the community in need, and assi ance for employees who are fully dedicated to the company. This research uses a quantitative approach with interview techniques with the PKBL Division Manager and documentation udies on the company’s o cial social media where the PKBL team publishes the social programs that have been implemented. This research found that PT TWC through the PKBL Division of corporate social responsibility programs is ill conventional in nature and not relevant enough to the company’s operational activities that focus on temple tourism parks. PT TWC should be able to involve the community in the process of program formulation through open dialogue so that the issues that become the basis of material of the social programs can be truly targeted both in terms of the community being targeted and the priority of the issue itself. Future udies can use other research techniques such as observation and interviews with the community around the company to get a perception of PT TWC.